EXHUMATION OF THE HELLENIC ACCRETIONARY PRISM – EVIDENCE FROM FISSION-TRACK THERMOCHRONOLOGY - Marsellos, A.E; Kidd, W.S.F; Garver, J.I.; Kyriakopoulos, K.G. (Bulletin of the Geological Society of Greece, 2010)
Below the Potamos extensional detachment fault exposed in northern Kythera, the phyllite-quartzite unit (PQU) shows very consistent zircon FT cooling ages of c.11 Ma reflecting the time just after the rapid exhumation through the brittle-ductile transition. In contrast, a wide range of Mesozoic and some Paleozoic zircon FT cooling ages from Eocene-Oligocene Tripolis and Pindos flysch sandstones from above the detachment reflect sedimentary source ages. Early Miocene apatite fissiontrack cooling ages characterize the flysch sandstones, and show that early Miocene exhumation affected rocks above the detachment. The thermotectonic evolution of the flysch of Tripolis and Pindos units within the rocks above the Potamos detachment on Kythera is reconstructed using zircon and apatite fission-track (FT) thermochronology. The apatite FT data provide evidence for a burial depth of at least 6km for the samples, which were reset. Burial was not deeper than 11km, since the zircon fission-track system in the same rocks was not reset. The exposed rocks of Tripolis and Pindos flysch on Kythera represent part of an accretionary wedge with a burial shortly after deposition in or near the subduction trench, and a cooling history due to exhumation of the flysch in the early Miocene. The subsequent Mid-Late Miocene exhumation of the PQU unit follows from beneath the (mostly carbonate) Tripolis and Pindos sedimentary rocks.